Tinjauan Pustaka Faktor-Faktor yang Mempengaruhi Perilaku Seks Pranikah pada Remaja Berdasarkan Teori Health Belief Model (HBM) - Salwa Octavia; Luqman Effendi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Premarital sexual behavior among adolescents remains a public health concern influenced by social change, technological development, and social environment. This study aims to analyze factors associated with adolescent premarital sexual behavior based on the Health Belief Model (HBM). A systematic literature review was conducted on eight studies published between 2019 and 2025, including journal articles, undergraduate theses, and a doctoral dissertation. The findings were analyzed by categorizing the results into six HBM components: perceived susceptibility, perceived severity, perceived benefits, perceived barriers, cues to action, and self-efficacy. The results indicate that perceived susceptibility is the most consistently associated component with adolescent premarital sexual behavior. Perceived severity, perceived barriers, cues to action, and self-efficacy also show significant associations in several studies, whereas perceived benefits demonstrate the weakest and most inconsistent relationship. Overall, adolescent premarital sexual behavior is shaped by the interaction between risk perception, environmental support, and individual confidence in behavioral control. These findings confirm that the Health Belief Model remains a relevant framework for designing adolescent health promotion and preventive interventions.